Sensitivity of Mass Distribution with Respect to Pitch Motions of High-Speed Craft - Sumardiono Sumardiono; I Putu Arta Wibawa (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2023)
Beside of environmental conditions, ship characteristics also greatly affect in ship behavior when operating at sea, called seakeeping ability. The shape of the hull, appendages, damping, and the weight distribution of ship are some of the factors that determine how the ship motion response occurred. This paper examines how much the pitch motion is influenced in high-speed craft due to the changing of the gyration radius. By using the strip theory method, and by taking the irregular head sea condition and a wave height of 4 meters, then the ship speed and the wave period are varied to determine the pitch motion amplitude at 3 values ​​of gyration radius: 0.2, 0.25 and 0.3 of the ship's length. The results of the study show that at higher ship speeds, the gyration radii greatly influence the pitch amplitude. As for changes in the wave period, the influence is significant at value of 5 second. From these two results, it is clear that the ship's gyration radii must be determined precisely to be able to predict an accurate pitch motion response on a high-speed craft.